Habitat suitability modeling of a Subterranean mammal in Iran: case study of the Western Mole-Vole (Ellobius lutescens) - Naqibzadeh, Abbas; Németh, Attila (Acta Agraria Debreceniensis, 2025)
Rodentia is the largest order of mammals in Iran, distributed in almost all types of habitats. Subterranean mammals, such as the Western Mole-Vole, have an important role as ecosystem engineers by creating underground burrows and tunnels and aerating, propagating seeds, and building shelter for other small mammals and animals. They are also a keystone part of the food source for other prey vertebrates. However, many areas are considered pests, and their habitats are fragmented due to human activities, which causes a reduction in their habitats and colonization. Habitat Modeling tools help us to predict a suitable niche for conservation planning. The purpose of this study is to predict habitat suitability for Western Mole-Vole in Iran by using the MaxEnt method to determine which part of Iran is a desirable habitat for this species. The result indicated that the northwest of Iran, especially the southern slopes of the Alborz Mountains and the Eastern slopes of the Zagros Mountains, provides suitable habitats for the western Mole-Vole. The environmental variables that are more influenced by the distribution of this species are elevation of 1800 to 2500 meters, human activities such as roads, and rainfed farms. Approximately 7% of Iran is a suitable habitat for the Western Mole-Vole.